PENGARUH KONSENTRASI DAN SELANG WAKTU PEMBERIAN PUPUK DAUN AGROKING 2000 TERHADAP PERTUMBUHAN SETEK TEH TRI 2025 (Camellia sinensis (L). O. Kuantze). - M. H. Bintoro; Yudi Herdiana; Salwa L. Dalimunthe (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1994)
This experiment was carried out at Gambung Experimental Station from January till June 1993. The objective of this experiment was to study the effect of Agro King 2000 concentration compare with Gemari 2 ml L-1 and intervals application on tea cutting node growth. The experiment was arranged in Factorial Randomized Block Design. It consisted of two factors and three replications. The first factor was Agro King 2000 concentrations 1 ml L -1, 2 mL -1, 3 ml L -1 , 4 ml L-1, and 2 ml Gemari L-1 as control. The  second factor was Gemari and Agro King interval applications at 2, 3 and 4 weeks application.  . Interval application treatments and various concentrations of Agro King 2000 and Gemari and the interaction of both treatments did not significantly affect on all tea cutting node growth variables. It means Gemari and Agro King can be used for tea cutting node. This experiment suggested that 2 mIL-1  Gemari or 1 miL-1 Agro King2000 for every 4 weeks could be used for tea cutting node.